Pyroptosis in sepsis: Comprehensive analysis of research hotspots and core genes in 2022 - Xia, Demeng; Wang, Sheng; Yao, Renqi; Han, Yuexue; Zheng, Liyu; He, Pengyi; Liu, Ying; Yang, Lu (Frontiers in Molecular Biosciences, 2022)
Sepsis, a life-threatening disease caused by dysregulated host response to infection, is a major public health problem with a high mortality and morbidity rate. Pyroptosis is a new type of programmed cell death discovered in recent years, which has been proved to play an important role in sepsis. Nevertheless, there is lack of comprehensive report and analysis to help researchers get quick overview and find meaning hotspots. In thus, we aimed to identify the study status and knowledge structures of pyroptosis in sepsis and summarize the key mechanism of pyroptosis in sepsis. Data were retrieved and downloaded from the WOS database. Software such as VOSviewer was used to analyze these publications. Key genes were picked out by using (https://www.genecards.org) and (http://www.bioinformatics.com). These key genes were then performed by Gene Ontology (GO) enrichment analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis and Protein-Protein Interaction (PPI) network analysis. From 2011 to 2021, a total of 299 papers met the search criteria and the global interest of pyroptosis in sepsis measured by the value of RRI started to increase since 2016. China ranking first in the number of publications followed by USA, the Univ Pittsburgh in the United States had the highest number of publications among the institutions. The journal of Frontiers in immunology published the most related articles. Through keywords co-occurrence analysis, the high-frequency subject terms were divided into 3 clusters like “animal research”, “cell research” and“molecular research”clusters. “mir”, “aki”, “monocyte”, “neutrophil” were the newest keywords that may be the hotspot. In addition, a total of 15 genes were identified as hub genes. TNF, IL-1β, AKT1, CASP1, STAT3 were highly expressed in lung tissues, thymus tissues, and lymphocytes. PPI network analysis revealed that promoting sepsis inflammation through Toll and NOD signaling pathways is the main role of pyroptosis in sepsis. KEGG analysis indicated that pyroptosis may exert a vital role in sepsis via the NOD, PI3K/AKT, MAPK/JNK pathway. Through the quantitative analysis of the literature on pyroptosis in sepsis, we revealed the current status and hotspots of research in this field and provide some guidance for further studies